The Modern Mercenary : Private Armies and What They Mean for World Order - McFate, Sean (New York Oxford University Press, 2017)
Former industry insider Sean McFate lays bare the opaque world of private military contractors, explaining the economic structure of the industry and showing in detail how firms operate on the ground
Include Index and Bibliography
Keywords: Mercenary troops -- Military policy -- United States